Determining Factors of Sustainable Agriculture Practices: A Case Study in East Java - Shaleh, Mohammad Ilyas; Muhaimin, Abdul Wahib; Toiba, Hery (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Environmental unfriendly agriculture has become a major concern in various countries due to population growth, climate change, and excessive use of natural resources. It is important to adopt sustainable farming practices such as organic farming, wise natural resource management, and environmentally friendly technologies to enhance productivity without harming the surrounding environment. This research aims to identify the factors influencing farmers' adoption of sustainable agricultural practices in East Java, Indonesia. The study was conducted in Lawang, Malang Regency, East Java, through direct surveys and interviews with farmers using questionnaires. Data analysis was performed using the multivariate probit (MVP) method to identify factors affecting the adoption of sustainable agricultural practices. The results indicate that education, land area, side jobs, and partnerships have a positive and significant impact on the adoption of sustainable farming practices such as the use of organic fertilizers. However, farming experience and participation in communal activities have a negative impact on the adoption of such practices. Farmers with higher education levels, larger land areas, side jobs, and partnerships are more likely to adopt sustainable farming practices. Conversely, farmers with longer farming experience and active participation in communal activities tend to be less interested in adopting these practices.